2016
DOI: 10.1007/s00408-016-9849-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy (SBRT) with Lower Doses for Selected Patients with Stage I Non-small-cell Lung Cancer (NSCLC)

Abstract: SBRT is very effective for stage I NSCLC. Biologically effective doses (BED) >100 Gy are recommended. Elderly patients and those with a limited performance status may not tolerate these high doses. This study investigated the outcomes after lower dose SBRT (BED < 90 Gy) in 46 patients with stage I NSCLC, who were aged ≥70 years or in reduced general condition. Local control rates at 1, 2, and 3 years were 100, 95, and 95 %, respectively. Rates of freedom from distant progression were 83, 63, and 54 %, and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…One phase 3 study comparing SBRT and surgery (only the SBRT data was used) [12], 10 phase 2 [20-31], 1 phase 1 [32], and 56 retrospective [33-51,53-89] photon SBRT studies were included in the survival outcome comparison analysis. Among them, treatment-related toxicities were reported in all the prospective studies [12,20-32], and 40 retrospective studies [34,37,39-40,42,44-47,49,52-61,65,67-73,76-78, 80-82,84-89]. These studies were included in the treatment-related toxicity comparison analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One phase 3 study comparing SBRT and surgery (only the SBRT data was used) [12], 10 phase 2 [20-31], 1 phase 1 [32], and 56 retrospective [33-51,53-89] photon SBRT studies were included in the survival outcome comparison analysis. Among them, treatment-related toxicities were reported in all the prospective studies [12,20-32], and 40 retrospective studies [34,37,39-40,42,44-47,49,52-61,65,67-73,76-78, 80-82,84-89]. These studies were included in the treatment-related toxicity comparison analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting data on the use of surveillance chest imaging stem from debate over detection of recurrence versus second primary lung cancer and synchronous versus metachronous primary lesions. The growing use of stereotactic body radiation therapy in the treatment of recurrence (34)(35)(36) and/or metachronous cancers (37) and second primary lung cancers (38) may help redefine the role of surveillance in patients with lung cancer.…”
Section: Original Researchmentioning
confidence: 99%
“…This report demonstrated the feasibiliy of SBRT to synchronous lung nodules. Furthermore, several studies have shown feasibility of lower dose SBRT for recurrent lung cancer, with local control rates of up to 96% at one year and freedom from distant progression rate at 74% at one year and 65% at two years …”
Section: Factors Favoring Sbrtmentioning
confidence: 99%